2011
DOI: 10.4141/cjps09190
|View full text |Cite
|
Sign up to set email alerts
|

Using a polyploid meiosis stability (PMeS) line as a parent improves embryo development and the seed set rate of a tetraploid rice hybrid

Abstract: He, Y.-C., Ge, J., Wei, Q., Jiang, A.-M., Gan, L., Song, Z.-J. and Cai, D.-T. 2011 Using a polyploid meiosis stability (PMeS) line as a parent improves embryo development and the seed set rate of a tetraploid rice hybrid. Can. J. Plant Sci. 91: 325–335. Polyploidy is widely accepted to play an important role in the evolution and breeding of plant species. However, a low seed set rate significantly hindered the development of polyploid rice breeding. Our results show that the seed set rate in polyploid meiosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Unlike Dendranthema nankingense and Dracocephalum kotschyi (Liu et al 2011;Zahedi et al 2014), the total number of flowers per inflorescence, fruits per infructescence and seeds per fruit of the tetraploid J. curcas were all significantly decreased compared with the diploid (Table 4). This may have been because the pollen fertility of the tetraploid was low (He et al 2010(He et al , 2011, or because the tetraploid plants did not produce enough photosynthetic product (Rekika…”
Section: Resultsmentioning
confidence: 99%
“…Unlike Dendranthema nankingense and Dracocephalum kotschyi (Liu et al 2011;Zahedi et al 2014), the total number of flowers per inflorescence, fruits per infructescence and seeds per fruit of the tetraploid J. curcas were all significantly decreased compared with the diploid (Table 4). This may have been because the pollen fertility of the tetraploid was low (He et al 2010(He et al , 2011, or because the tetraploid plants did not produce enough photosynthetic product (Rekika…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it is beneficial to improve the effectiveness of polyploidy breeding in the genus Populus, according to the experience of parent selection in hybridization breeding [76]. Polyploidization is essential in speciation, evolution, and creating elite varieties for poplar plantations [77][78][79]. Moreover, triploid Populus is more widely used for the production of lumber, fiber, and fuel, in contrast to diploids [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…As a basic feature in nearly all plant species, polyploidization normally results in a higher yield than that of diploid plants and is regarded as a powerful tool in crop breeding (Ramanna and Jacobsen 2003). During the last decade, the application of polyploidization has been used in rice breeding, and several highly productive hybrid rice lines have been developed (Cai et al 2007;He et al 2011;Ghaleb et al 2020). Through comparative studies between diploid and autotetraploid rice cultivars, it was shown that there are higher glutelin contents in autotetraploid cultivars than in diploid cultivars (Cai 2011).…”
Section: )mentioning
confidence: 99%